2021
DOI: 10.1002/jlb.3ma0821-015r
|View full text |Cite
|
Sign up to set email alerts
|

Iron deprivation restrains the differentiation and pathogenicity of T helper 17 cell

Abstract: Iron plays a critical role in immune responses. However, its role in T helper cell differentiation and function remains poorly understood. In this study, it is shown that the restraint of iron availability through blocking CD71‐mediated iron endocytosis impaired the differentiation and pathogenicity of TH17 cells. Administrations of anti‐CD71 mAb could relieve the development of experimental autoimmune encephalomyelitis (EAE). Mechanistically, the iron deficiency due to the blocking of CD71 enhanced IL‐2 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
2
3
1
Order By: Relevance
“…Although anti-CD71 treatment did not affect the viability of T H 17 cells, anti-CD71 interfered with their differentiation, in agreement with other recent work ( 29 ). The percentage of IL-17 + cells was significantly reduced compared with controls (fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Although anti-CD71 treatment did not affect the viability of T H 17 cells, anti-CD71 interfered with their differentiation, in agreement with other recent work ( 29 ). The percentage of IL-17 + cells was significantly reduced compared with controls (fig.…”
Section: Resultssupporting
confidence: 92%
“…In support of this, iron-deficient mice failed to develop experimental autoimmune encephalomyelitis (EAE) ( 63 ), and a CD4 T cell–specific deletion of Tfrc also failed to drive T H 17 neuroinflammation via decreased granulocyte-macrophage colony-stimulating factor mRNA stability ( 64 ). CD71 blockade was previously shown to inhibit T H 17 differentiation partly by increasing IL-2 secretion ( 29 ), but our T H 17 cell cultures did not produce significantly more IL-2 upon anti-CD71 treatment. T H 17 cultures from SLE-prone mice demonstrated a higher propensity for T H 17 cell differentiation, which was associated with altered expression of key iron metabolism genes.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Previous study demonstrated that peroxiredoxin six overexpression eliminated high-glucose induced ferroptosis, which was reflected in the inhibition of iron accumulation and the increased expression of SLC7A11 and GPX4 ( Zhang et al, 2021 ). Previous study revealed that the restraint of iron availability through blocking CD71-mediated iron endocytosis damaged the differentiation and pathogenicity of TH 17 cells ( Li et al, 2021 ). We did not examine the changes of iron death-related factors such as SLC7A11, CD71, ACSL4 and GPX4.…”
Section: Discussionmentioning
confidence: 99%
“…Given the breadth and conserved nature of pathways involving iron interacting proteins it follows that iron deprivation would likely have broad implications on cell biochemistry, health, and function with potential knock-on effects at the tissue or systemic levels. Our work explains why iron depletion potently suppresses T-cell responses in models of immunisation, infection, and autoimmunity 5,17,4648 . We also propose that the iron deficiency-associated perturbations described here may in part be responsible for cellular dysfunction in other cell types and tissues during iron deficiency.…”
Section: Discussionmentioning
confidence: 75%